Assessment of thyroid parameters in Alcoholic liver disease - DR. LAVITA D’COSTA; DR. CHITRA Y. DHUME (International Journal of Pharma and Bio Sciences, 2016)
Normal level of thyroid hormone is important for normal hepatic function as it maintains the metabolism of bilirubin by playing a role in the enzymatic activity of glucuronyl transferase and by regulating the level of ligandin. The liver in turn glucuronidates and sulphates the thyroid hormone, excretes into bile and regulates their systemic endocrine effects. Therefore, hepatic dysfunction is commonly observed in patients with thyroid disease. Mean levels of Gamma-glutamyl transferase are increased in alcoholic cirrhosis with alcohol abuse of < 10 years duration. In this study thyroid function tests and liver function tests were performed on the 200 subjects, of which 100 subj ects were patients with Alcoholic Liver Disease, 100 were healthy controls and it was found that the serum triâ€iodothyronine and free triâ€iodothyronine levels were decreased and levels of Thyroid stimulating hormone were increased in patients with Alcoholic Liver Disease as compared to controls.